Sera from severe trauma patients with pneumonia and without infectious complications have differential effects on neutrophil biology. Issue 1 (December 2016) - Relja, B.; Taraki, R.; Teuben, M.; Mörs, K.; Wagner, N.; Wutzler, S.; Hildebrand, F.; Perl, M.; Marzi, I.
Abstract Background Major trauma patients (TP) developing imbalanced immune response are at high risk for infectious post-injury complications including pneumonia. Neutrophils play a central role in the host defense against bacteria and thereby pathogenesis of infections. While there are numerous studies about neutrophil function after trauma, data about their biology in patients who suffer from pneumonia following trauma are sparse. Here, we studied the effect of serum isolated from patients who do and do not develop infection (inf.) on the biology of neutrophils from healthy volunteers. Methods Sera samples from eighteen TP with an injury severity score above 16 were obtained. Nine patients were grouped tono inf. group (TP without pneumonia), and nine toinf . group (TP with pneumonia). Samples were obtained at admission to emergency department (ED), a day prior pneumonia diagnosis (1 d prior inf ) or at the day of diagnosis (1 d prior inf ). Samples from the equal post-injury days in the correspondingno inf . group were used. Neutrophils from nine healthy volunteers were isolated. Effects for sera isolated from infected and non-infected patients on neutrophil biology were analyzed. Migratory capacity of neutrophils towards TP's serum, their CD11b and CD62L membrane receptor expression and oxidative burst activity after stimulation with TP's serum were determined and compared between groups. Results Migratory capacity of neutrophils was significantly increased after trauma and persisted during the study period. CD11b expression in all groups was significantly increased. CD62L expression decreased generally in samples from ED and recovered later to baseline. Stratifyingno inf . andinf . groups showed significantly decreased migratory capacity, increased CD11b and significantly decreased CD62L expression in theno inf . group. These differences persisted during the complete observational period. ROS production was strongly reduced in theno inf . group compared to theinf . group at later experimental time points. Conclusions This data indicate that patients at risk for pneumonia development have differentially and early activated neutrophils following trauma compared to patients who are not at risk for post-injury complication. Studies about the differential biology of neutrophils and their immediately after trauma modified activity depending on the post-injury clinical course are warranted, and may deliver predictive or even therapeutic strategies to control inflammation.